Lembang Fault Deformation Study Using Sentinel-1A Image with Ps-Insar Method - Rian Nurtyawan; Rizky Berzata Sigiro (Publikasi Indonesia, 2024)
Badan Nasional Penanggulangan Bencana (BNPB) states that the earthquakes that have occurred in the territory of Indonesia during 2018 were 11,418. Nearly 95 percent of earthquakes occur in fault areas and plate boundaries. In West Java, especially in the Bandung area there is a fault structure called the Lembang Fault which is mostly occupied by community settlements. The Lembang Fault is an active fault, therefore it is necessary to conduct research related to monitoring the Lembang Fault for disaster mitigation purposes. One of parameter to determine the level of activity of a fault is deformation. The amount of deformation can be analyzed through the remote sensing methods, one of them is the Persistent Scatterer Interferometric Synthetic Aperture Radar (PS-InSAR) method. In this study the main data used is Sentinel-1A image data consist of eight scenes with acquisition time from January 2018 to March 2019. The results of the study concluded that the average deformation that occurred along the Lembang Fault was 2,485 mm with a graph that tends to rise. The area most affected by deformation is Cisarua Subdistrict with Line-of-Sight velocity of deformation of 28.4 - 48.9 mm / year. While the smallest deformation occurred in Lembang District with Line-of-Sight velocity of deformation of -2.3 - 19.2 mm / year.